Simulation by the finite element method of the wind turbine blade material under the influence of the variable wind force - DEGHOUM Khalil; GHERBI Mohammed taha (University Of Eloued جامعة الوادي, 2020)
Wind turbines are an essential source of renewable energy so we did this study to determine the appropriate material for blade where we worked on two materials CFRP and GFRP as one of the materials used where, we simulated by the program ansys as a professional program in the simulation process and choose the finite elements method FEM As a means of reaching the stress and strain and the deformation, This simulation was performed under the influence of variable winds according to weather, starting from 1500 to 4000 N as the maximum value of these materials. Through this process, any materials that were more resistant were extracted to give us a greater lifespan and more return to the wind turbine.
Intervention
Keywords: wind turbine; CFRP; GFRP; FEM; blade; material